Microglia are not protective against cryptococcal meningitis - Sally H. Mohamed; Man Shun Fu; Sofia Hain; Alanoud Alselami; Eliane Vanhoffelen; Yanjian Li; Ebrima Bojang; Robert Lukande; Elizabeth R. Ballou; Robin C. May; Chen Ding; Greetje Vande Velde; et al. (Nature Communications, 2023)
Abstract Microglia provide protection against a range of brain infections including bacteria, viruses and parasites, but how these glial cells respond to fungal brain infections is poorly understood. We investigated the role of microglia in the context of cryptococcal meningitis, the most common cause of fungal meningitis in humans. Using a series of transgenic- and chemical-based microglia depletion methods we found that, contrary to their protective role during other infections, loss of microglia did not affect control of Cryptococcus neoformans brain infection which was replicated with several fungal strains. At early time points post-infection, we found that microglia depletion lowered fungal brain burdens, which was related to intracellular residence of C. neoformans within microglia. Further examination of extracellular and intracellular fungal populations revealed that C. neoformans residing in microglia were protected from copper starvation, whereas extracellular yeast upregulated copper transporter CTR4. However, the degree of copper starvation did not equate to fungal survival or abundance of metals within different intracellular niches. Taken together, these data show how tissue-resident myeloid cells may influence fungal phenotype in the brain but do not provide protection against this infection, and instead may act as an early infection reservoir.